The Impact of Lactobacillus reuteri on Oral and Systemic Health: A Comprehensive Review of Recent Research - Zihui Liu; Qing Cao; Wenqing Wang; Bowen Wang; Yilun Yang; Cory J. Xian; Tiejun Li; Yuankun Zhai (Microorganisms)
Oral diseases, particularly dental caries and periodontal disease, pose significant global health challenges. The imbalance of the oral microbiota plays a key role in the occurrence of these diseases, prompting researchers to seek new strategies to restore oral ecological balance. Lactobacillus reuteri is a Gram-positive rod-shaped bacterium that exists in various body parts of humans, including the gastrointestinal tract, urinary tract, skin, and so on. This species has a potentially positive impact on oral health and plays an important role in maintaining systemic health. Recent studies have explored the application of Lactobacillus reuteri in the prevention and treatment of oral diseases, and its impact on systemic health has also been preliminarily revealed. The current review summarizes the role of Lactobacillus reuteri in oral health and systemic health and outlines its potential applications in the future. Lactobacillus reuteri has shown promising prospects in treating non-communicable biofilm-dependent oral diseases, but its mechanism of action and efficacy still need further research. In addition, Lactobacillus reuteri has also displayed some potential benefits in promoting overall health. Future research should focus on revealing the specific pathways of action of Lactobacillus reuteri, screening for the most beneficial strains, determining the most effective drug delivery strategies, developing oral and systemic health products based on Lactobacillus reuteri, and ensuring their safety in clinical applications.